Image-based calibration of rolling resistance in discrete element models of sand. (March 2021) - Rorato, R.; Arroyo, M.; Gens, A.; Andò, E.; Viggiani, G.
Abstract: Models that introduce rolling resistance at the contact are widely employed in simulations using the discrete element method (DEM) to indirectly represent particle shape effects. This approach offers substantial computational benefits at the price of increased calibration complexity. This work proposes a method to simplify calibration of rolling resistance. The key element is an empirical relation between a contact parameter ( rolling friction ) and a 3D grain shape descriptor ( true sphericity) . Values of true sphericity can be obtained by image analysis of the grains, either directly by 3D acquisition or by correlation with simpler-to-obtain 2D shape measures. Evaluation of rolling friction is thus made independent from that of other model parameters. As an extra benefit, the variability of grain shape in natural sands can be directly mapped into the discrete model. A mapping between rolling friction and true sphericity is calibrated using specimen-scale and grain scale results from two triaxial compression tests on Hostun sand and Caicos ooids. The mapping is validated using different triaxial tests from the same sands and from other reference sands (Ottawa, Ticino). In the case of Ticino grain-shape acquisition is made in 2D, using an ordinary table scanner. The results obtained support this direct calibration procedure.